Teacher-Perceived Factors Affecting the Sustainability of Formative Feedback Practices - Dowlatshahi, Nazanin (Assessment and Practice in Educational Sciences, 2023)
This study aimed to explore the teacher-perceived factors that influence the sustainability of formative feedback practices in secondary school classrooms. The research employed a qualitative design grounded in an interpretive paradigm to examine the experiences of 29 secondary school teachers in Tehran. Participants were selected using purposive sampling to ensure relevant experience with formative assessment practices. Data were collected through in-depth, semi-structured interviews and analyzed using thematic analysis. The coding process followed open, axial, and selective coding stages, supported by the use of NVivo software. Data collection continued until theoretical saturation was reached, and ethical protocols including informed consent and confidentiality were strictly observed. Analysis revealed three main themes: (1) teacher beliefs and professional identity, (2) institutional and structural support, and (3) student engagement and response. Within these themes, subcategories such as growth-oriented mindsets, feedback confidence, workload constraints, leadership support, peer collaboration, student receptivity, and feedback literacy emerged as key factors influencing sustainability. Teachers described formative feedback as a dynamic and reflective process shaped by their educational philosophy, institutional culture, and student behaviors. The sustainability of feedback practices depended on the interplay of internal motivation, systemic facilitation, and student participation. Sustaining formative feedback requires more than individual commitment; it necessitates coherent policy support, school leadership, professional development, and student readiness. Teachers’ identities, confidence, and collaboration with peers enhance feedback persistence, while institutional constraints and student disengagement pose significant barriers. Enhancing feedback sustainability will involve empowering teachers and students alike within a supportive and aligned educational ecosystem.